2011
DOI: 10.1534/genetics.110.125138
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Interaction Between hedgehog and Notch Promotes Proliferation at the Anterior–Posterior Organizer of the Drosophila Wing

Abstract: Notch has multiple roles in the development of the Drosophila melanogaster wing imaginal disc. It helps specify the dorsal-ventral compartment border, and it is needed for the wing margin, veins, and sensory organs. Here we present evidence for a new role: stimulating growth in response to Hedgehog. We show that Notch signaling is activated in the cells of the anterior-posterior organizer that produce the region between wing veins 3 and 4, and we describe strong genetic interactions between the gene that encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…Using a ubiquitous driver, we first confirmed that our Psn shRNA lines result in 80-90% reduction of mRNA levels (Figure 1) and recapitulate developmental phenotypes of Psn germ-line mutant flies (Struhl and Greenwald 1999;Chung and Struhl 2001;Mahoney et al 2006). Consistent with notching wings in Notch heterozygous mutant flies, and in wing-specific Notch or Psn KD flies (Boyles et al 2010;Casso et al 2011), wing disc-specific expression of Psn shRNA leads to similar wing phenotypes at varying severity, allowing selection of the most effective Psn shRNA line (Figure 2). Selective neuronal expression of two independent Psn shRNA lines beginning at embryonic stages caused earlier lethality, rough eye phenotypes, and severe climbing defects (Figure 3 and Figure 4), and these phenotypes were partially rescued by expressing a Drosophila Psn transgene ( Figure 5).…”
Section: Discussionsupporting
confidence: 64%
“…Using a ubiquitous driver, we first confirmed that our Psn shRNA lines result in 80-90% reduction of mRNA levels (Figure 1) and recapitulate developmental phenotypes of Psn germ-line mutant flies (Struhl and Greenwald 1999;Chung and Struhl 2001;Mahoney et al 2006). Consistent with notching wings in Notch heterozygous mutant flies, and in wing-specific Notch or Psn KD flies (Boyles et al 2010;Casso et al 2011), wing disc-specific expression of Psn shRNA leads to similar wing phenotypes at varying severity, allowing selection of the most effective Psn shRNA line (Figure 2). Selective neuronal expression of two independent Psn shRNA lines beginning at embryonic stages caused earlier lethality, rough eye phenotypes, and severe climbing defects (Figure 3 and Figure 4), and these phenotypes were partially rescued by expressing a Drosophila Psn transgene ( Figure 5).…”
Section: Discussionsupporting
confidence: 64%
“…Notch was first identified in Drosophila as an important gene for wing development (de Celis and GarciaBellido, 1994). It is required for the establishment of the dorsal-ventral compartment border, and the proper development of wing margin, veins, and sensory organs (Casso et al, 2011). The Notch receptor is activated by the Delta and Jagged/Serrate families of membrane-bound ligands (Weinmaster, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Both the notum and anterior wing margin primordia are predominantly in the A compartment, and genes that are known to function in neuronal development (such as acheate and scute ) are therefore expected to be expressed at high levels in A cells. Furthermore, because A cells at the A/P compartment border depend upon activation of the Notch pathway (Casso et al 2011), Notch pathway components might also be expressed in greater levels in A cells. The A subcluster from the array analysis did include achaete and scute as well as the Notch pathway components Enhancer of spilt complex transcripts m7 , m4 , and γ.…”
Section: Resultsmentioning
confidence: 99%